1996
DOI: 10.1063/1.1147274
|View full text |Cite
|
Sign up to set email alerts
|

An improved CO2 laser intracavity photoacoustic spectrometer for trace gas analysis

Abstract: This work describes an improved CO2 laser intracavity photoacoustic spectrometer. It can detect and measure small quantities of trace gases in air. The measured absorption sensitivity of 3.3×10−10 cm−1 corresponds to a mixture of 11 pptv (volume parts per trillion) of ethene in nitrogen. The sensitivity and reliability of the instrument were enhanced by reducing the level of background signals originating from optical and acoustical sources. The sensitivity reached is comparable with the best existing continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
0
8
1
1
Order By: Relevance
“…From this table it clearly results that the best sensitivity is obtained in our extracavity PA instrument, where a min (cm À1 ) is better by one or two orders of magnitude than with intracavity arrangements. The minimum detectable concentration obtained by us is four times lower than that obtained by Harren et al [12] and 50 times lower than that reported by Fink et al [17].…”
Section: Low Laser Powercontrasting
confidence: 39%
See 1 more Smart Citation
“…From this table it clearly results that the best sensitivity is obtained in our extracavity PA instrument, where a min (cm À1 ) is better by one or two orders of magnitude than with intracavity arrangements. The minimum detectable concentration obtained by us is four times lower than that obtained by Harren et al [12] and 50 times lower than that reported by Fink et al [17].…”
Section: Low Laser Powercontrasting
confidence: 39%
“…Most published papers give values between 37 and 200 V cm/W [10,12,[15][16][17] and only few reports obtained similar values [2,14] or a higher value [13] (by using a microphone with a very large responsivity).…”
Section: Low Laser Powermentioning
confidence: 76%
“…In order to test whether or not the previously reported xylanase‐induced (minor component of crude cellulysin) ethylene biosynthesis [30, 31]in leaf tissue of N. plumbaginifolia can be also provoked in P. lunatus , the gas phase of cellulysin‐treated leaves was analysed by photoacoustic spectroscopy (PAS) [32]. The method is highly sensitive for several low molecular compounds (detection limit for ethylene: 0.03 μg m −3 ) and allows a continuous monitoring of the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…The ethylene production was measured with a photoacoustic laser spectrometer consisting of a line‐tunable infrared CO 2 ‐laser and a resonant photoacoustic cell [32, 33]. The background free detection method allows the detection of ethylene at concentrations at a pptv (volume parts per trillion) level.…”
Section: Methodsmentioning
confidence: 99%
“…Die dortigen Erfahrungen waren eine wesentliche Anregung für den Aufbau eines Labors in unserer Arbeitsgruppe [6]. Das Blockschaltbild eines solchen Messplatzes ist in Abb.…”
Section: Vom Spektrometer Zum Messsystemunclassified